Black tea markets worldwide: Are they integrated? - Yong-mei XU; Fang-bin QIAO; Ji-kun HUANG (Journal of Integrative Agriculture, 2022)
Global tea consumption has risen significantly alongside rapid expansion of international trade in recent years. However, few studies have systematically examined the relationship among the major tea markets worldwide. Using weekly data from 2012–2019, this study empirically analyzed the price series of the world's major black tea auction markets. The estimation results showed that these markets are connected, even though heterogeneities vary. This finding holds not only for regional markets but also for international markets. The findings offer important implications for tea-producing countries with millions of smallholder farmers.